(untitled) (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2019)
INTRODUCTION: This research aims to determine the use of musical headphones and the knowledge of the Faculty of Health of Basic Sciences and the Faculty of Arts and Humanities of the University of Pamplona headquarters, because the use of headphones at high intensities is directly related with the risk of hearing damage. METHODS: Taking into account the nature of the problem and the objective, this research has a quantitative approach of a descriptive type. The sample selection was made by sim-ple random sampling with respect to the total number of students of the faculties mentioned above, as well as the fulfillment of the inclusion and exclusion criteria. RESULTS: Regarding the use of the headphones, 90% of the students do it improperly and 10% adequately, 80% of the students do not know the effects that the headphones cause on their health. ANALYSIS AND DISCUSSION: The analysis shows that a large part of the population makes inappropriate use and are unaware of the health ef-fects that these devices can cause. CONCLUSIONS: a high rate of excessive use of musical headphones was observed in students belonging to the Faculty of Health, Basic Sciences and Faculty of Arts and Humanities. Therefore, lies the importance of raising awareness among students about the harmful ef-fects caused by the excessive use of headphones and contributing to the early diagnosis in case there is any type of hearing impairment for the improvement of optimal hearing health.